Development of ESL Reading Comprehension Assessment System For Malaysian Year Five Students - Chang, Kuan Lim (2018)
The present study focused on the development of an ESL reading comprehension assessment system for Malaysian Year Five students. The current Malaysian Primary school achievement test assigns a composite grade to summarise students‟ performance. The composite grades do not provide any specific information with regards to each student‟s reading ability. In this study, the ESL reading comprehension assessment system includes the development of standardised generic reading comprehension test, reading matrix and reading performance descriptors. The standardised generic reading comprehension test consists of three sections with reading comprehension questions at elementary, intermediate and advanced levels based on Barrett‟s and Bloom‟s Taxonomy in line with the Malaysian English Language Syllabus and Standard Curriculum Document and Assessment. Each section of the test contains linear and non-linear texts with literal, reorganisation and inferential comprehension questions. The standardised generic reading comprehension test was piloted and the researcher proceeded to develop the reading matrix by determining the cut score for each band and the number of bands. A Reading Matrix is a chart that ESL teachers match their students‟ test scores with educational levels. The administration of the standardised generic reading comprehension test involved Year Five respondents from primary schools located in Larut, Matang and Selama. The data gathered was analysed for the development of reading performance descriptors illustrating the reading sub-skills the students have and have not acquired.